Genetic characterization of indigenous East African cattle breeds using microsatellite DNA markers - Okomo, M.A.; Rege, J.E.O.; Teale, A.J.; Hanotte, Olivier H. (International Committee for World Congresses on Genetics Applied to Livestock Production, 1998)
Seven cattle populations indigenous to East Africa and three reference breeds (Sahiwal, N'Dama and Friesian) were characterized with 18 autosomal microsatellite loci. Within-breed diversity was high in all breeds with observed heterozygosities ranging from 0.511 (+ or -) 0.214 (N'Dama) to 0.660 (+ or -) 128 (Friesian). All populations, except the Kenya Boran were at Hardy-Weinberg equilibrium. Nei's standard genetic distance (Ds) ranged from 0.023 (+ or -) 0.009 (Danakil and Abigar) to 0.868 (+ or -) 0.200 (N'Dama and Sahiwal). An UPGMA tree built up from Ds genetic distances revealed the following clusters: the Friesian and N'Dama breeds (Bos taurus from Europe and Africa, respectively) were clustered together but they were clearly separate populations, while the Sahiwal breed (Bos indicus) native to Asia was more closely related to the East African breeds than to the N'Dama and Friesian. No clear genetic distinction was evident between the East African humped (Zebu and Sanga) and the humpless (Sheko) breeds. Allele specific analysis suggested taurine influence in the East African Zebu breeds, and an indicine influence in the East African taurine (Sheko). The results indicated that all East African cattle studied, while genetically separate, contained both indicine and taurine backgrounds. Their unique genetic identity calls for their conservation and utilisation.